Thyroid Hormones and Pregnant Women - Audu Jonah; Simon P Abriba; Solomon Matthias Gamde; Abubakar Hamida; Usman Kingsley (Journal of Current Research and Studies, 2025)
Background: Thyroid illness is a group of disorders affecting the thyroid gland. The thyroid is a small, butterfly-shaped gland at the front of your neck that produces thyroid hormones, since thyroid hormones regulate how our bodies use energy; they have an impact on practically every physical organ, including the pulse. The hormones thyroid creates play a key role in regulating our metabolism the way our body uses energy along with temperature, weight, cholesterol levels and other key body functions. Thyroid disorders may be present before pregnancy, or they may develop during pregnancy. Being pregnant does not change the symptoms of thyroid disorders. How the fetus is affected depends on which thyroid disorder present and which medications are used for treatment. Because thyroid hormones are essential for the healthy development of the baby's brain and nervous system, babies who are dependent on other sources for their thyroid hormones during the first trimester may be born with neurological development issues. Objectives: the purpose of the study of thyroid hormone and pregnancy are to emphasis on the relationship between thyroid hormone and pregnancy, and the impacts of thyroid dysfunction on maternal and fetal health during pregnancy. Method: This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Review (PRISMA-ScR) guidelines. Using search keywords like prostate cancer, risk factors, screening, and preventative approaches, scholarly papers published in electronic databases including PubMed, Scopus, and Google Scholar from 2004-2025 were obtained for the review Conclusion: thyroid dysfunction during pregnancy is a key area of focus in clinical endocrinology. For babys brains and neurological system to develop normally, thyroid hormones are essential, they depends on thyroid hormone supply, which is delivered by the placenta during the first trimester. Healthy women can develop slightly high thyroid hormone during pregnancy. Thyroid problems can be hard to diagnose in pregnancy due to higher levels of thyroid hormones and other symptoms that occur in both pregnancy and thyroid disorders. Thyroid hormones that are high can harm the mother’s health and the baby’s.